From telemark to carving - Nikola Stojanović; Zvezdan Savić; Vlado Stijepović; Ljubiša Lilić (University of Banja Luka, Faculty of physical education and sport, 2017)
Skiing belongs to the group of specific cyclical sports which include the learning, improvement and realization of different motor skills and activities, and as such is inextricably linked to snow-covered terrain at higher altitudes. The exact time when skiing was first invented is unknown, but what is known is that its development throughout history was complex, both in terms of skiing equipment and in terms of technique. The first skis date back to the ice age, 4500 BC, and were of various length, weight and width. Only one ski pole was used. Telemark and Christiania skiing were the basic skiing techniques of turning and stopping which are still being developed and improved to this very day. The position and stances of the skiers have undergone changes and are closely related to ski design and the design of the accompanying equipment. Longer skis of various lengths have been replaced by two shorter skis of the same length, modern automatic buckles, deeper and sturdier ski boots and two shorter identical poles. Competitive skiing has developed and changed in accordance with the requirements of the competition (the carve turns, the length and radius of the skis, their shape, size, the number of and distance between the poles, the quality of the skiing surface, differences in elevation along the ski slope, etc.). A short, heavy and rigid ski was replaced in the 1960's by a more narrow and longer ski, only to be replaced once again during the 1990's by a shorter, more lightweight and wider carving ski. New technological challenges facing the ski industry are once again bound to the more narrow, lightweight and faster skis, but also to the combination of shorter and longer skis which are used in beginner training. Thus, this research deals with the historical representation of current techniques and professional and technical practices in skiing, but also the predictions of future trends in the development of Alpine skiing.